2011
DOI: 10.1038/hr.2011.115
|View full text |Cite
|
Sign up to set email alerts
|

Roles of central renin-angiotensin system and afferent renal nerve in the control of systemic hemodynamics in rats

Abstract: Afferent renal nerves (ARNs) convey signals generated by physiological changes in the kidney to the central nervous system. The aim of this study was to determine whether ARNs contribute to cardiovascular regulation through central renin-angiotensin system (RAS)-dependent pathways. Blood pressure and renal sympathetic nerve activity (RSNA) were monitored during elevations in pelvic pressure in anesthetized Wistar-Kyoto Izm (WKY) rats and spontaneously hypertensive Izm rats (SHRs). In both groups of rats, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Extensive pieces of evidence have demonstrated that central RAS plays a critical role in regulating the central sympathetic outflow (Fujisawa et al, 2011;Zucker et al, 2014). Reports indicate that central AngII, via activation of local AT1Rs, significantly augments the central sympathetic outflow, which can be effectively suppressed by AT1R antagonists (Yoshimura et al, 2000;Campese et al, 2002;Gao et al, 2004;Fujisawa et al, 2011;Zucker et al, 2014). Meanwhile, the balance between central ACE and ACE2 in the brain also has a major influence on the central regulation of sympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive pieces of evidence have demonstrated that central RAS plays a critical role in regulating the central sympathetic outflow (Fujisawa et al, 2011;Zucker et al, 2014). Reports indicate that central AngII, via activation of local AT1Rs, significantly augments the central sympathetic outflow, which can be effectively suppressed by AT1R antagonists (Yoshimura et al, 2000;Campese et al, 2002;Gao et al, 2004;Fujisawa et al, 2011;Zucker et al, 2014). Meanwhile, the balance between central ACE and ACE2 in the brain also has a major influence on the central regulation of sympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in renal blood flow, which was induced by excessive activation of renal sympathetic nerves in patients with HF, has been shown to activate the renal afferent nerves involved in the regulation of central sympathetic outflow to the heart and peripheral circulation system (Calaresu and Ciriello, 1981;Xu et al, 2012;Booth et al, 2015;Xu et al, 2015). It has been shown that central RAS plays a crucial role in the regulation of central sympathetic outflow (Fujisawa et al, 2011;Zucker et al, 2014). The RDN technique has been shown to reduce the wholebody noradrenaline spillover (Schlaich et al, 2009) and muscle sympathetic nerve activity (MSNA) (Hering et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Then, ICV injection of vildagliptin was performed using an injector needle (30 gauge stainless steel), as described previously. 21,22 Briefly, under isoflurane anesthesia, a guide cannula was implanted into the left cerebroventricular region for ICV infusion. Rats were placed on a stereotaxic frame (Narishige Scientific Instruments, Tokyo, Japan) in the prone position and the guide cannula was fixed to the skull.…”
Section: Methodsmentioning
confidence: 99%
“…Beneficial effects of RASBs on the CV system include inhibition of cardiac remodeling, reduction in central sympathetic outflow, enhancement of sympathetic‐inhibitory responses to baroreceptor stimulation, and improvement in endothelial function, among others . CCBs also have some beneficial CV effects.…”
Section: Discussionmentioning
confidence: 99%